We have to find the straight line passing through the points ( -3,2) and ( 5,8)

The equation of a line passing through the points ( x1, y1) and ( x2, y2) is given by ( y - y1) = [ ( y2 - y1)/(x2 - x1)]*( x - x1).

...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the straight line passing through the points ( -3,2) and ( 5,8)

The equation of a line passing through the points ( x1, y1) and ( x2, y2) is given by ( y - y1) = [ ( y2 - y1)/(x2 - x1)]*( x - x1).

Here ( y2 - y1)/(x2 - x1) is the gradient of the line.

Substituting the values we have we get :

( y - y1) = [ ( y2 - y1)/(x2 - x1)]*( x - x1)

=> ( y - 2) = [ ( 8 - 2)/(5 + 3)]*( x + 3)

=> ( y - 2) = ( 6)/8)*( x + 3)

=> y - 2 = (3/4)*( x+ 3)

=> 4y - 8 = 3x + 9

=> 3x - 4y + 17 = 0

The gradient is 3/4

**The required equation of the line is 3x - 4y + 17 = 0 and its gradient is 3/4.**